Essential tremor-challenged maxillary rehabilitation using a digitally guided all-on-six implant restoration: a case report - Zhang, Shuning; Cui, Jiarui; He, Fan; Hu, Jiani; Yang, Guangzheng; Huang, Hui; Wang, Jie; Jiang, Xinquan (Frontiers in Oral Health, 2025)
This case report describes a 73-year-old female with essential tremor who experienced significant dissatisfaction with her maxillary complete denture. Her tremor-related dexterity impairment limited her ability to manage removable prostheses, while the excessive denture volume severely disrupted speech. Moreover, her neuromuscular condition made it challenging to adapt to a new occlusal scheme. To address these issues, a digitally guided all-on-six implant-supported prosthesis was delivered under local anesthesia, preserving her pre-existing, neuromuscularly adapted occlusion with minor esthetic adjustments to the anterior teeth. At the 1-year follow-up, the patient reported high satisfaction with both esthetics and function, along with improved speech and masticatory efficiency. This report underscores the value of digital workflows in maintaining functional adaptation and providing predictable prosthodontic solutions for patients with neuromuscular impairments.